2013
DOI: 10.1109/tbme.2013.2257772
|View full text |Cite
|
Sign up to set email alerts
|

Postinfarction Ventricular Tachycardia Substrate Characterization: A Comparison Between Late Enhancement Magnetic Resonance Imaging and Voltage Mapping Using an MR-Guided Electrophysiology System

Abstract: Catheter ablation of ventricular tachycardia (VT) is preceded by characterization of the myocardial substrate via electroanatomical voltage mapping (EAVM). The purpose of this study was to characterize the relationship between chronic myocardial fibrotic scar detected by multicontrast late enhancement (MCLE) MRI and by EAVM obtained using an MR-guided electrophysiology system, with a final aim to better understand how these measures may improve identification of potentially arrhythmogenic substrates. Real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…These findings are in line with findings of Nakahara et al [ 13 ], where a higher concentration of abnormal EGMs (late potentials) was found in the putative isthmus and also with Hsia et al [ 7 ], where the majority of these delayed and fractionated endocardial electrogram recordings were found in critical central pathway sites. In this study we did not report nor conduct a rigorous correlation study between low-voltage and MR-defined dense scar, since it was the focus of our previous publication [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are in line with findings of Nakahara et al [ 13 ], where a higher concentration of abnormal EGMs (late potentials) was found in the putative isthmus and also with Hsia et al [ 7 ], where the majority of these delayed and fractionated endocardial electrogram recordings were found in critical central pathway sites. In this study we did not report nor conduct a rigorous correlation study between low-voltage and MR-defined dense scar, since it was the focus of our previous publication [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bipolar recordings were made with the distal electrode pair (1 and 2). The catheters were placed in the (right ventricle) RV or LV using active catheter tracking with MR-guidance as reported previously [ 15 ]. The catheters were advanced under full MR guidance with a 3D LV shell created from segmentation of SSFP-cine images acquired in the same session, with the animal resting in the same position; this eliminated the need for additional registration or alignment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NICM patients also display distinctive electrogram (EGM) characteristics: The distribution of LAVA in NICM is typically epicardial, since almost all LAVA appear in low‐voltage areas . Correlation between low‐voltage area, LAVA signals, and ischemic scar on MRI has been demonstrated …”
Section: Introductionmentioning
confidence: 97%
“…D uring ventricular tachycardia ablation, bipolar electrogram voltage amplitude is widely used for myocardial substrate characterization and for determining relevant therapeutic strategies. [1][2][3][4][5] Josephson and Anter recently highlighted the pitfalls of interpreting bipolar electrogram voltages as a medium for substrate mapping by identifying myriad factors that significantly affect its measurement. 6,7 These factors can be classified into those that can and cannot be standardized.…”
mentioning
confidence: 99%